Determine the frequency distribution of hepatocellular carcinoma (HCC) and evaluation of viral persistence in the development of HCC among Pakistani patients - Resham , Saleha; khan, Moomal; Rahman , Eeman; Adnan, Fazal; Manzoor, Sobia (Journal of the Pakistan Medical Association, 2025)
Objective: To determine the frequency distribution of hepatocellular carcinoma, and to evaluate viral persistence and its association with viral titers. Method: The retrospective study was conducted at the Lahore Hepatobiliary/Liver Transplantation Unit, Shaikh Zayed Hospital, Lahore, Pakistan, and comprised data between December 2010 and September 2019 related to patients with liver complications. For viral persistence evaluation, immunohistochemistry analysis was performed on explanted liver tissues/liver resections from patients who also had hepatitis B and C, assessing hepatitis C virus nonstructural protein 5B and hepatitis B virus X protein expression using qualitative immunohistochemistry scoring. Data was analysed using R version 3.3.5. Results: Of the total 1,384 patients admitted, hepatocellular carcinoma was noted in 256(18.5%) cases, with age and gender being significantly different between positive and negative patients (p<0.05). Further, 81% of hepatocellular carcinoma patients with hepatitis C had immunohistochemistry score 1), followed by 13% with score 3, and 6% score 2 with respect to hepatitis C virus nonstructural protein 5B protein expression. In hepatocellular carcinoma patients with hepatitis B, 40% had score 1), 40% had score 2, and 20% had score 3 with respect to hepatitis B virus X protein expression. Conclusion: Hepatocellular carcinoma was found to be the most frequently reported liver-associated disease, predominantly affecting males. Viral protein detection in viral-induced hepatocellular carcinoma samples underscored the persistence of the virus in hepatocytes. Key Words: Hepatitis, Hepatocellular carcinoma, NS5B, HBX, Liver neoplasm, Hepacivirus.